2023
DOI: 10.14336/ad.2023.0222
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β as A Master Regulator of Aging-Associated Tissue Fibrosis

Abstract: Fibrosis is the abnormal accumulation of extracellular matrix proteins such as collagen and fibronectin. Aging, injury, infections, and inflammation can cause different types of tissue fibrosis. Numerous clinical investigations have shown a correlation between the degree of liver and pulmonary fibrosis in patients and telomere length and mitochondrial DNA content, both of which are signs of aging. Aging involves the gradual loss of tissue function over time, which results in the loss of homeostasis and, ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 156 publications
0
2
0
1
Order By: Relevance
“…Clinical studies have also confirmed the accumulation of T-regulatory lymphocytes in connection to chronological aging and the association of T-regulatory cells with immunosenescence [41,42]. The expansion of T-regulatory lymphocytes and myeloid derived suppressor cells (MDSC), promotes an increase in TGFβ which is a key regulator of physiological and pathological aging, fibrosis and atherogenesis [43].…”
Section: Discussionmentioning
confidence: 90%
“…Clinical studies have also confirmed the accumulation of T-regulatory lymphocytes in connection to chronological aging and the association of T-regulatory cells with immunosenescence [41,42]. The expansion of T-regulatory lymphocytes and myeloid derived suppressor cells (MDSC), promotes an increase in TGFβ which is a key regulator of physiological and pathological aging, fibrosis and atherogenesis [43].…”
Section: Discussionmentioning
confidence: 90%
“…The dysregulation of the TGF-β1/Smad pathway plays an essential role in the pathological process of silicosis [ 44 , 46 ]. TGF-β1 recruits and activates transforming growth factor beta receptor 1(TGFR1) upon binding to TGF-β receptor 2 (TGFβR2).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LVH often results from chronic pressure overload, which can be exacerbated by the arterial stiffness seen in arteriosclerosis and atherosclerosis [ 15 , 16 , 32 ]. Renal senescence might further compound these effects through the interplay of hypertension, dysregulated volume control, and hormonal disturbances affecting cardiovascular health [ 33 , 34 , 35 ]. Clinically, this finding highlights the necessity for a comprehensive approach to managing elderly patients with LVH.…”
Section: Discussionmentioning
confidence: 99%